2002
DOI: 10.3354/meps236023
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria and Foraminifera: key players in a short-term deep-sea benthic response to phytodetritus

Abstract: The deep-sea floor has long been considered a 'food desert' but recent observations suggest that episodic inputs of relatively fresh organic matter (phytodetritus) occur and that benthic processing of this material may be rapid. Although the responses of the total community in terms of oxygen consumption and of some individual benthic groups have been identified, the quantitative role of the different groups in the short-term response remains largely unknown. We examined the short-term response in major benthi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
195
4
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(225 citation statements)
references
References 50 publications
23
195
4
3
Order By: Relevance
“…We did not determine the biomass of microbes and meiofauna, which have higher reproduction and growth rates and are thus more likely to show a detectable shortterm biomass increase in response to organic matter input (Soltwedel 2000;Rex et al 2006). We did not find an increase in foraminifera biomass over the seasonal transition as it has been reported from other investigations (Altenbach 1992; Moodley et al 2002). Our restriction to individuals of macrofaunal size may explain the deviation from processes described for foraminifera communities elsewhere, since total communities in those studies where dominated by meiofaunal species of smaller size and presumably faster metabolic reactions.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…We did not determine the biomass of microbes and meiofauna, which have higher reproduction and growth rates and are thus more likely to show a detectable shortterm biomass increase in response to organic matter input (Soltwedel 2000;Rex et al 2006). We did not find an increase in foraminifera biomass over the seasonal transition as it has been reported from other investigations (Altenbach 1992; Moodley et al 2002). Our restriction to individuals of macrofaunal size may explain the deviation from processes described for foraminifera communities elsewhere, since total communities in those studies where dominated by meiofaunal species of smaller size and presumably faster metabolic reactions.…”
Section: Discussionsupporting
confidence: 53%
“…All macrofaunal foraminifera except for five individuals were agglutinated forms. For sorting, we used the method described by Moodley et al (2002) based on the presence of cytoplasma and appearance of shells. Biomass of macrofaunal foraminifera was estimated from abundance figures using an average value of 5 lg C individual -1 (Altenbach 1985).…”
Section: Macrobenthic Biomassmentioning
confidence: 99%
“…This lack of 20 knowledge hampers a realistic assessment of the role and importance of deep-sea nematodes in benthic energy flows, not only at the specific and generic levels, but also at trophic group and community levels. Feeding experiments, such as pulse-chase experiments, have proven successful in addressing feeding ecology questions Moodley et al, 2002;Witte et al, 2003a;Witte et al, 2003b), but nematode community results for the deep-sea remain variable. 25…”
Section: Nematode Feeding Selectivitymentioning
confidence: 99%
“…Nematodes, therefore, provide an ideal taxon for studying food-web structure and dynamics (Carman and Fry, 2002). Although the use of 13 C enriched carbon sources in experimental pulse-chase setups has proven to be an effective way of unravelling the fate of organic C in deep-sea sediments (Buhring et al, 2006;Levin et al, 1999;Moodley et al, 2002;Witte et al, 2003a), deepsea nematodes tend to be underrepresented in stable-isotope studies, mainly because large numbers of individuals need to be collected to obtain sufficient biomass for analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on benthic foraminifera have shown that they are dormant for most of the year, but increase their activity as soon as food is available (e.g. Moodley et al (2002)). At this time they also build their new chambers and/or reproduce.…”
Section: Vital Parameters 431 Respiration Ratementioning
confidence: 99%